Retail Investor Sentiment and Behavior An Empirical Analysis - Burghardt, Matthias (Gabler, 2011)
Investor sentiment and behavior play an important role in financial markets. Using a unique data set consisting of more than 36.5 million submitted retail investor orders over the course of five years, Matthias Burghardt constructs an innovative retail investor sentiment index. He shows that retail investors trading decisions are correlated, that retail investors are contrarians, and that a profitable trading strategy can be based on these aggregated sentiment measures.